Problematika dan Upaya Penyelesaian Desa Lengkap di Kabupaten Klaten - Wulansari, Harvini; widiyantoro, susilo; Widodo, Sri (Tunas Agraria, 2024)
The Complete Systematic Land Registration (PTSL) program aims to increase the quantity and quality of land data in Indonesia; however, PTSL activities tend to prioritize quantity over quality of land parcels, including mapping of Category 4 (K4) land parcels. This research was conducted in Klaten Regency by taking samples from PTSL activities in 2020 and 2021. The aim of this research was to determine the quality of land data and the obstacles faced by the Klaten Regency Land Office in improving the quality of K4 land data. The method used is descriptive-qualitative. The research results show that the quality of land data in every village in Klaten Regency is above 99% complete. However, in completing the Complete Village, there were several obstacles in the form of internal and external obstacles. Internal constraints include: (1) variations in the quality of spatial data in registration maps; (2) limited human resources; and (3) a limited number of measurement letter archives that can be uploaded to the KKP, while external constraints include: (1) lack of availability of land data in villages or sub-districts; (2) relatively new village apparatus; and (3) a large number of state land statuses in one region. Various efforts were made to complete the complete village, namely: (1) determining priorities for the complete village based on physical and administrative conditions; (2) a land census involving all stakeholders; (3) land plot mapping based on the position and size of the latest land plot; and (4) careful handling of documents and comparative studie   Program Pendaftaran Tanah Sistematis Lengkap (PTSL) bertujuan untuk meningkatkan kuantitas dan kualitas data pertanahan di Indonesia, namun kegiatan PTSL cenderung mementingkan kuantitas daripada kualitas bidang tanah, termasuk pemetaan bidang tanah Kategori 4 (K4). Penelitian ini dilakukan di Kabupaten Klaten dengan mengambil sampel hasil kegiatan PTSL pada tahun 2020 dan 2021. Tujuan dari penelitian ini adalah untuk mengetahui kualitas data pertanahan dan kendala yang dihadapi oleh Kantor Pertanahan Kabupaten Klaten dalam meningkatkan kualitas data pertanahan K4. Metode yang digunakan yaitu kualitatif deskriptif. Hasil penelitian menunjukkan bahwa kualitas data pertanahan di setiap desa di Kabupaten Klaten di atas 99% lengkap. Namun demikian, dalam penyelesaian Desa Lengkap terdapat beberapa kendala yang dihadapi berupa kendala internal dan eksternal. Kendala internal meliputi: (1) Keberagaman kualitas data spasial di peta pendaftaran; (2) Keterbatasan sumber daya manusia; (3) Keterbatasan jumlah arsip Surat Ukur yang dapat diunggah ke KKP, sedangkan kendala eksternal antara lain : (1) Kurangnya ketersediaan data pertanahan di desa/kelurahan; (2) Perangkat desa yang tergolong baru; (3) Jumlah status tanah negara yang besar dalam satu wilayah. Berbagai upaya dilakukan untuk penyelesaian Desa Lengkap yaitu : (1) Penetapan prioritas desa lengkap berdasarkan kondisi fisik dan administrasi; (2) Sensus pertanahan dengan melibatkan seluruh stakeholder; (3) Pemetaan bidang tanah berbasis posisi dan ukuran bidang tanah terbaru; dan (4) Penanganan dokumen secara hati-hati dan studi banding.